Distribution, characterization and identification of superficial fungal pathogens isolated from various body sites of symptomatic and asymptomatic farmers of Indang and Amadeo , Cavite. - Cruzate, Sherine M. (2013)
ABSTRACT see Upload (MT BIO 063 2013)